Will Grayson, Will Grayson - Green, John, 1977- (Dutton, 2010)
When two teens, one gay and one straight, meet accidentally and discover that they share the same name, their lives become intertwined as one begins dating the other's best friend, who produces a play revealing his relationship with them both.